2023
DOI: 10.3390/educsci13010071
|View full text |Cite
|
Sign up to set email alerts
|

Effects of COVID-19 Pandemic on Students’ Written Outcomes: An Interior Architecture Research/Theory Module Case Study in the UK

Abstract: Different learning methods (online, blended, blended-online and face-to-face) have been examined widely since the late 1990s. Although many design studies discuss engagement with these new methods in relation to studio modules, research/theory modules have not been investigated yet for interior architecture with both qualitative and quantitative data as a holistic approach. This study reveals how the new blended online learning method and the COVID-19 pandemic affected students’ written outcomes in a research/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
(110 reference statements)
0
2
0
Order By: Relevance
“…This study identified several key challenges, including technological barriers, difficulties in adapting to new teaching methods, and reduced opportunities for hands-on learning. 23 A recent study examined the impact of the pandemic on interior design students’ learning experience. The study found that students faced significant challenges in adapting to online learning but also identified several strategies that could be used to enhance their learning experiences in the future.…”
Section: Discussionmentioning
confidence: 99%
“…This study identified several key challenges, including technological barriers, difficulties in adapting to new teaching methods, and reduced opportunities for hands-on learning. 23 A recent study examined the impact of the pandemic on interior design students’ learning experience. The study found that students faced significant challenges in adapting to online learning but also identified several strategies that could be used to enhance their learning experiences in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Other stressors—consistent with previous virus outbreak research—included frustration, boredom, insufficient supplies, inadequate information, and negative stigmatization (Brooks et al, 2020). Within education, the pandemic accelerated difficult technological change, promoted new but long-lasting ways of working and learning, and produced sustainable modes of blended learning (Antunes & Barreto, 2022; Metinal & Ayalp, 2022; Ulusoy, 2023).…”
Section: Introductionmentioning
confidence: 99%